The Petroleum Industry and Socio-political Change in Mauritania: 2001-2011 - de Vietri, Max (Curtin University, 2014)
The thesis focuses on the interaction of the nascent oil industry and the changing political character of Mauritanian between 2001 and 2011. The theoretical starting point is the hypothesis of the ‘oil curse’. Historically-rooted contextual causes, such as the relationship between state and long-standing tribal and ethnic institutions, are found of greater influence to socio-political instability than the establishment of the oil industry. Foreign interference is found to also be a precipitant of political upheavals.